The Intelligent Automated Pressure-Adjustable Orthosis for Patients With Adolescent Idiopathic Scoliosis: A Bi-Center Randomized Controlled Trial. Issue 20 (15th October 2020) - Lin, Yangmin; Lou, Edmond; Lam, Tsz Ping; Cheng, Jack Chun-Yiu; Sin, Sai Wing; Kwok, Wing Kwan; Wong, Man Sang
Abstract : Study Design: Randomized controlled trial. Objective: To compare the effectiveness of the automated pressure-adjustable orthosis (PO) and conventional orthosis (CO) for treatment of adolescent idiopathic scoliosis (AIS). Summary of Background Data: Orthosis wearing quality may influence its effectiveness for AIS. An automated PO aimed to provide a more optimized and consistent biomechanical environment. Clinical evaluation was conducted to study the effectiveness of this innovative orthosis. Methods: Patients with AIS who met the criteria (Age 10–14, Cobb 20°–40°, and Risser sign 0–2) were recruited from two clinics and randomly assigned to the PO and CO groups. Compliance sensors were embedded in both groups, while the PO group was set to adjust the interfacial pressure as prescribed automatically. Clinical assessments (radiology and quality of life, QoL) were conducted at the baseline, immediate after orthosis fitting and 1-year follow-up. Orthosis wearing compliance was tracked using thermo and pressure sensors. Results: Twenty-four patients were enrolled with one drop-out (PO, n = 11; CO, n = 12). Significant immediate in-orthosis correction was observed in the PO (11.0° ± 6.5°, 42.0%, P < 0.001) and CO (10.3° ± 5.3°, 37.6%, P < 0.001) groups. After 1 year, no patient with PO progressed while two with CO had progression more than 5°. The mean daily wearing duration was 1.1 hours longer in the PO group as compared with the CO group (15.4 ± 4.5 vs. 14.3 ± 3.8 h). Moreover, the wearing quality within the targeted pressure was 33.9% higher in the PO group (56.5 ± 16.5% vs. 23.1 ± 12.1%, P < 0.001). No significant difference in the QoL results was observed between two groups nor within both groups during the study period. Conclusion: This study showed that the automated PO could enhance wearing quality when compared with the CO, thus offering a better biomechanical corrective effect in the study period without adverse effect on the patients' wearing quantity and QoL. Level of Evidence: 1